Building the British Atlantic World : Spaces, Places, and Material Culture, 1600-1850 - Herman, Bernard L., 1951-; Maudlin, Daniel (Book collections on Project MUSE., 2016)
"Spanning the North Atlantic rim from Canada to Scotland, and from the Caribbean to the coast of West Africa, the British Atlantic world is deeply interconnected across its regions. ... studying the interplay between physical construction and social themes that include identity, gender, taste, domesticity, politics, and race, the authors interpret material culture in a way that particularly emphasizes the people who built, occupied, and used the spaces and reflects the complex cultural exchanges between Britain and the New World"--